Avoiding Two Elements of S3\C2 in Sn\Ck. - Phillipson, Mitch; Williams, Tristan (My University, 2009)
We build on previous research into pattern avoidance in colored permutations. This study presents a conjecture on the number of Wilf classes and their associated sizes for avoiding two patterns of length three with two colors.
Avoidance of Colored Patterns: Wilf Classes and Enumeration.
Color poster with text, table, and equations.
Keywords: Combinatorial analysis; Combinatorial enumeration problems; Permutations; Posters